2017
DOI: 10.1016/j.ijhcs.2016.08.005
|View full text |Cite
|
Sign up to set email alerts
|

On predicting learning styles in conversational intelligent tutoring systems using fuzzy decision trees

Abstract: Intelligent Tutoring Systems personalise learning for students with different backgrounds, abilities, behaviours and knowledge. One way to personalise learning is through consideration of individual differences in preferred learning style. OSCAR is the name of a Conversational Intelligent Tutoring System that models a person's learning style using natural language dialogue during tutoring in order to dynamically predict, and personalise, their tutoring session. Prediction of learning style is undertaken by cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(66 citation statements)
references
References 51 publications
0
63
0
3
Order By: Relevance
“…The appropriate teaching methods of student LS will enable students to accept and understand the concepts taught, and contribute to better achievement indirectly [36], [37], [38]. [26] reported that by identifying learning style, making each of student know of their strengths and weaknesses in learning and they have the option to personalize their learning environment.…”
Section: Learning Style Detectionmentioning
confidence: 99%
“…The appropriate teaching methods of student LS will enable students to accept and understand the concepts taught, and contribute to better achievement indirectly [36], [37], [38]. [26] reported that by identifying learning style, making each of student know of their strengths and weaknesses in learning and they have the option to personalize their learning environment.…”
Section: Learning Style Detectionmentioning
confidence: 99%
“…Fuzzy trees have been induced to predict the learning style of individuals. Outcome classification has been observed due to the automatic behavior of learning from a collection of data [16].…”
Section: Related Workmentioning
confidence: 99%
“…In other words, decision tree models are so transparent that people can clearly identify how outputs are mapped from inputs (Liu et al 2015(Liu et al , 2016c. In practice, applications of decision tree learning are extensive and varied, such as text classification (Khan et al 2015), biomedicine (Tayefi et al 2017), intelligent tutoring systems (Crockett et al 2017) and transient stability assessment (Rahmatian et al 2017).…”
Section: Related Workmentioning
confidence: 99%